Peran Waffen Schutzstaffel: Divisi Das Reich dalam Operasi Barbarossa 1941 - Fauzi, Muhammad Rizqi (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
AbstractThis article is entitled The Role of Waffen Schutzstaffel: The das Reich Division in Operation Barbarossa 1941. The background in this study is based on the researchers' curiosity about the German-Soviet War during WW II and in particular the role of the ss das Reich division in Barbarossa operations. This study aims to describe and analyze the role of the das Reich division in Operation Barbarossa 1941. The method used in this thesis research is a historical method by conducting four research steps namely heuristics, criticism, interpretation, and historiography as well as data collection techniques using literature studies. The results of this thesis research can be drawn conclusions include: First, beginning with the formation of the SS Stabswache as Hitler's personal guard force which later developed into the das Reich division. Second, Broadly speaking Germany uses a blitzkrieg strategy by dividing its three forces. The das Reich division during Operation Barbarossa was placed in the Herengruppe Center. Third, the struggle of the das Reich division during the Barbarossa operations had a good effect on every attack carried out by the Germans. The conclusion begins with only a small army which then develops into an independent division and has been trained in various battles until its peak in Operation Barbarossa is able to give everything that is best to carry out the task. Researchers hope that in the future this research can be used for positive things.